A cryostat-based frozen section method to increase the yield of extracellular vesicles extracted from different tissues - Shuangzhu Yang; Weiwei Qin; Xiangji Li; Qingdong Guo; Yuan Wang; Jing Chen; Hongmei Li; Shutian Zhang; Li Min (BioTechniques, 2022)
Extracellular vesicles (EVs) are small vesicles mediating intercellular communications that have been widely used in disease diagnosis. Extracting EVs from tissues is of great importance, but current approaches are finite and the EV yield is limited. Here, the authors introduced a new method to increase EV yield based on frozen sectioning. With a standardized, semiautomated tissue-slicing procedure in a cryostat, the authors successfully isolated EVs from hearts, kidneys and stomachs. The morphology, size distribution and purity of those isolated EVs were evaluated. Additionally, compared with the traditional scalpel section method, they confirmed the higher yield of tissue-derived EVs with the cryostat-based method. The authors believe that the new method they developed would largely facilitate the research and clinical application of EVs.